Erythroid anion transport, nitric oxide, and blood pressure - Hsu, Kate (Frontiers in Physiology, 2024)
Glycophorin A and glycophorin B are structural membrane glycoproteins bound in the band 3 multiprotein complexes on human red blood cells (RBCs). Band 3 is an erythroid-specific anion exchanger (AE1). AE1-mediated HCO3− transport provides the substrate for the enzyme-catalyzed conversion HCO3−(aq) ⇌ CO2(g), which takes place inside the RBCs. Bicarbonate transport via AE1 supports intravascular acid–base homeostasis and respiratory excretion of CO2. In the past decade, we conducted several comparative physiology studies on Taiwanese people having the glycophorin variant GPMur RBC type (which accompanies greater AE1 expression). We found that increased anion transport across the erythrocyte membrane not only enhances gas exchange and lung functions but also elevates blood pressure (BP) and reduces nitric oxide (NO)-dependent vasodilation and exhaled NO fraction (FeNO) in healthy individuals with GP.Mur. Notably, in people carrying the GPMur blood type, the BP and NO-dependent, flow-mediated vasodilation (FMD) are both more strongly correlated with individual hemoglobin (Hb) levels. As blood NO and nitrite (NO2−) are predominantly scavenged by intraerythrocytic Hb, and NO2− primarily enters RBCs via AE1, could a more monoanion-permeable RBC membrane (i.e., GPMur/increased AE1) enhance NO2−/NO3− permeability and Hb scavenging of NO2− and NO to affect blood pressure? In this perspective, a working model is proposed for the potential role of AE1 in intravascular NO availability, blood pressure, and clinical relevance.